2011
DOI: 10.1089/jamp.2010.0845
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Lung Regions of Interest in Gamma Scintigraphy for Assessing Inhaled Therapeutic Aerosol Deposition

Abstract: Different approaches used to determine pulmonary regions of interest and quantify aerosol deposition produce different results. Our research highlights a genuine need for a consensus to standardize the methodology to facilitate data comparison between laboratories on aerosol deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 23 publications
3
47
0
1
Order By: Relevance
“…(67,68) In the previous validation study of Tian et al, (61) acceptable agreement was found between the in vivo results of Newman et al (62) and CFD computed airway predictions transferred to 2D planar images for the Novolizer inhaler, which was considered only at the PIFR of 99 LPM (fast inhalation), as well as a softmist inhaler also considered at a single flow rate. The methods established in the previous study of Tian et al (61) are repeated in the current study to evaluate the more challenging scenario of a single DPI evaluated at multiple flow rates generating different aerosol size distributions and tested in two separate airway geometries.…”
Section: Selection Of the In Vivo Dataset And Inhalation Waveformmentioning
confidence: 78%
See 1 more Smart Citation
“…(67,68) In the previous validation study of Tian et al, (61) acceptable agreement was found between the in vivo results of Newman et al (62) and CFD computed airway predictions transferred to 2D planar images for the Novolizer inhaler, which was considered only at the PIFR of 99 LPM (fast inhalation), as well as a softmist inhaler also considered at a single flow rate. The methods established in the previous study of Tian et al (61) are repeated in the current study to evaluate the more challenging scenario of a single DPI evaluated at multiple flow rates generating different aerosol size distributions and tested in two separate airway geometries.…”
Section: Selection Of the In Vivo Dataset And Inhalation Waveformmentioning
confidence: 78%
“…As described, the method used to segment the 2D planar image can influence the predictions of regional lung deposition, (67) and a newly recommend method for dividing planar images was described (68) after the publication of Newman et al (62) However, for validation purposes, the goal was to match the techniques used in the selected in vivo experiments as closely as possible. For the purpose of comparison, acceptable agreement between the CFD predictions and in vivo data will be determined based on the average relative error evaluated in the three regions of interest ( MT, C, and I+P) having a value of 15% or less.…”
Section: Deposition Fraction Calculations and Mappingmentioning
confidence: 99%
“…(126) Indeed, it was observed that larger particles visually deposited more proximally, whereas smaller particles distributed deeper into the lungs and had a greater penetration index. (125,148) The paradox of overall less total lung deposition with the 6 lm particles but greater efficacy in FEV 1 was explained by better matching of the inhaled therapeutic to its receptor distribution.…”
Section: Importance Of Aerosol Deposition Distribution To Clinical Efmentioning
confidence: 99%
“…29 Classically, scintigraphy underestimates the peripheral deposition due to the alveolar spaces included in the inner region due to how regions of interest are defined. 32 The choice of regions of interest was discussed in a recent recommendation. 24 Our results confirm that the Akita device offers a better method for drug administration to the peripheral lung compared with other modalities of nebulization, but they suggest that it is the device itself rather than the settings that are supposed to target differentially central or peripheral airways.…”
Section: Discussionmentioning
confidence: 99%